Quality of Life in Children with Atopic Dermatitis - Wicaksana, Muhammad Akbar; Suwarsa, Oki; Dwiyatnaningrum, Fenny (Althea Medical Journal, 2017)
Background: Atopic dermatitis (AD) is the most common chronic skin disease in children which caused significant morbidity and impaired quality of life (QoL). The main goal of AD therapy is to prevent flare -ups, prolong remission and increase QoL. Therefore, the study aimed to discover QoL in children with AD.Methods: The study was conducted at Pasundan Public Health Centre, Al Islam General Hospital and Kimia Farma Private Dermatology Clinic, from September to November 2015. This descriptive study used consecutive sampling with 24 outpatients who were admitted to the health facility and diagnosed as AD. A questionnaire on Infant Dermatitis Quality of Life for infants aged 0â4 years, and Children Dermatology Life Quality Index for children aged 5â16 years was used in this study to measure QoL.Results: Out of 24 patients, 9 patients aged 0â4 years had mean score of 4.44Â±4.36, and 15 patients aged 5â16 years had mean score of 5.80Â±3.95. Mean SCORAD Objective in patients aged 0â4 and 5â16 was 15.61Â±7.75 and 17.44Â±11.Conclusions: The QoL in children with AD vary among patients. Most of the patients have mild-moderate impairment in QoL.Â